The longest day - Wayne, John 1907-1979; Mitchum, Robert; Fonda, Henry 1905-1982; Albert, Eddie; Burton, Richard 1925-1984; Ryan, Cornelius
Re-enacts the military operation of D-Day from four points of view--the workings of the high commands of the American, English, French, and German forces in their battle scheme for Normandy. Largely filmed on actual invasion sites in France.